Update on tolerability and overall survival in COLUMBUS: landmark analysis of a randomised phase 3 trial of encorafenib plus binimetinib vs vemurafenib or encorafenib in patients with BRAF V600–mutant melanoma. (February 2020) - Ascierto, Paolo A.; Dummer, Reinhard; Gogas, Helen J.; Flaherty, Keith T.; Arance, Ana; Mandala, Mario; Liszkay, Gabriella; Garbe, Claus; Schadendorf, Dirk; Krajsova, Ivana; Gutzmer, Ralf; de Groot, Jan Willem B.; et al.
Abstract: Background: BRAF/MEK inhibitor combinations are established treatments for BRAF V600–mutant melanoma based on demonstrated benefits on progression-free survival (PFS) and overall survival (OS). Here, we report an updated analysis of the COLUMBUS (COmbined LGX818 [encorafenib] Used with MEK162 [binimetinib] in BRAF mutant Unresectable Skin cancer) trial with long-term follow-up. Methods: In part 1 of the COLUMBUS trial, 577 patients with advanced/metastatic BRAF V600–mutant melanoma, untreated or progressed after first-line immunotherapy, were randomised 1:1:1 to 450 mg of encorafenib QD + 45 mg of binimetinib BID (COMBO450) vs 960 mg of vemurafenib BID (VEM) or 300 mg of encorafenib ENCO QD (ENCO300). An updated analysis was conducted that included PFS, OS, objective response rate, safety and tolerability and analyses of results by prognostic subgroups. Results: At data cutoff, there were 116, 113 and 138 deaths in the COMBO450, ENCO300 and VEM treatment arms, respectively. The median OS was 33.6 months (95% confidence interval [CI], 24.4–39.2) for COMBO450, 23.5 months (95% CI, 19.6–33.6) for ENCO300 and 16.9 months (95% CI, 14.0–24.5) for VEM. Compared with VEM, COMBO450 decreased the risk of death by 39% (hazard ratio [HR], 0.61; 95% CI, 0.48–0.79). The updated median PFS for COMBO450 was 14.9 months (95% CI, 11.0–20.2), ENCO300 was 9.6 months (95% CI, 7.4–14.8) and VEM was 7.3 months (95% CI, 5.6–7.9). PFS was longer for COMBO450 vs VEM (HR, 0.51; 95% CI, 0.39–0.67). Landmark OS and PFS results show consistent results for each year analysed. Subgroups all favoured COMBO450 vs VEM. Conclusions: Updated PFS and OS results for COMBO450 from the COLUMBUS trial demonstrate a long-term benefit in patients with advanced BRAF V600–mutated melanoma. Highlights: MAPK pathway dual inhibition is the standard therapy in patients with BRAF V600 melanoma. Encorafenib + binimetinib demonstrated improved efficacy vs control arms. Encorafenib + binimetinib was generally well tolerated, with a distinct safety profile. Updated analysis suggested a durable response with encorafenib + binimetinib.